TFEB Gene Promoter Variants Effect on Gene Expression in Acute Myocardial Infarction - Zhang, Jie; Zhang, Yexin; He, Xiaohui; Wang, Shuai; Pang, Shuchao; Yan, Bo (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is involved in many physiological processes. Transcription factor EB (TFEB) is a master regulator of autophagy, and coordinates the expression of autophagic proteins, lysosomal hydrolases and lysosomal membrane proteins. Though autophagy has been implicated in several human diseases, little is known regarding TFEB gene expression and regulation in the process. Since dysfunctional autophagy plays critical roles in acute myocardial infarction (AMI), dysregulated TFEB gene expression may be associated with AMI by regulating autophagy. In this study, TFEB gene promoter was genetically and functionally analyzed in AMI patients (n=352) and ethnic-matched controls (n=337). A total of fifteen regulatory variants of TFEB gene, including eight single nucleotide polymorphisms (SNPs), was identified in this population. Among these, six regulatory variants [g.41737274T>C (rs533895008), g.41737144A>G, g.41736987C>T (rs760293138), g.41736806C>T (rs748537297), g.41736635T>C (rs975050638) and g.41736544C>T] were only identified in AMI patients. These regulatory variants significantly altered the transcriptional activity of the TFEB gene promoter. Further electrophoretic mobility shift assay revealed that three of the variants evidently affected the binding of transcription factors. Therefore, this study identified novel TFEB gene regulatory variants which effect gene expression. These TFEB gene regulatory variants may contribute to AMI development as a rare risk factor.